Hydroponic nutrient solution to cultivate of parsley and cerbiatta lettuce - Oliveira, Roberta Camargos; Ferraz Almeida , Risely; Eduardo Santos, José; Queiroz Luz, José Magno (Comunicata Scientiae, 2024)
Species that provide phytonutrients and bioactive compounds, such as parsley and lettuce, have gained prominence in a scenario of searches and concerns about maintaining health. Cultivation systems that enhance production in quantity and quality are essential. In this context, the objective of this study was to evaluate the development of parsley and lettuce under nutrient solution concentrations and plant position in the hydroponic system. The experiment was carried out in a randomized block design with five replications, in a 4 x 3 factorial scheme using four nutrient solution concentrations (50, 75, 100 and 125%) and three positions of the plants in the hydroponic profiles (initial, intermediate and final). Results showed that rates between 75 and 100% of nutrient solution presented higher production of cerbiatta lettuce and parsley in the hydroponic production. Channel position did not influence the cerbiatta lettuce production, but it influences the production parsley. Based on results conclude that is necessary different management to production of cerbiatta lettuce and parsley in hydroponic solution.